Investigation of the vortical flow around a reverse delta wing - Altaf, Afaq; Omar, Ashraf Ali E.; Asrar, Waqar; Ludin@Jamaluddin, Hani (2011)
A six component force balance was used to obtain the CL for a reverse delta wing and a delta wing for comparison purposes. A simulation of the streamlines, velocity vectors and surface pressure contours was carried out using CFD software to show the characteristics of the flow over a reverse delta wing.